Relações entre cultura e comprometimento organizacional: um estudo em duas empresas atuantes no mercado cearense - Cruz Neto, Alfredo Dias da (2010)
This job has searched to investigate the relations between the models from the organizational culture and the organizational commitment. The Methodological Theory Parameters used at this research was the models from the organizational culture from Cameron and Quinn (1996) and the models of organizational commitment from Meyer and Allen (1991). This study is characterized as an explorer research, descriptive, supported by bibliography research and documentary. This documentary research has been the base for a show definition and the understanding of the characteristics from the researched organizations. The research will happen at two company leaders of market participation on this segment which has worked in the State of Ceara. The basis collect will be done through a survey, subdivided in subjects of organizational culture profile, degrees of organizational commitment and the profile of the respondents, adopting a variation liket degree from 1 to 5 for the answers. The presentation methods and analysis from the degrees have been developed in three blocs. The first handles the interviewed profile for a way of a descriptive analysis, the second bloc identifies the predominant culture model and each organization researched in this job and the third bloc presents the categories of commitment at each of the organizations .The obtained results showed us, a predominate of innovated and market typology, in one of the researched companies and the predominant market typology in the second researched company. Thought the obtained results researched it was valued that the innovate culture relates definitely to the emotional commitment.